Prospects of Using High-Throughput Proteomics to Underpin the Discovery of Animal Host–Nematode Interactions - Tao Wang; Robin B. Gasser (Pathogens, 2021)
Parasitic nematodes impose a significant public health burden, and cause major economic losses to agriculture worldwide. Due to the widespread of anthelmintic resistance and lack of effective vaccines for most nematode species, there is an urgent need to discover novel therapeutic and vaccine targets, informed through an understanding of host–parasite interactions. Proteomics, underpinned by genomics, enables the global characterisation proteins expressed in a particular cell type, tissue and organism, and provides a key to insights at the host–parasite interface using advanced high-throughput mass spectrometry-based proteomic technologies. Here, we (i) review current mass-spectrometry-based proteomic methods, with an emphasis on a high-throughput ‘bottom-up’ approach; (ii) summarise recent progress in the proteomics of parasitic nematodes of animals, with a focus on molecules inferred to be involved in host–parasite interactions; and (iii) discuss future research directions that could enhance our knowledge and understanding of the molecular interplay between nematodes and host animals, in order to work toward new, improved methods for the treatment, diagnosis and control of nematodiases.